Radiobiological characterisation of a 28 MeV proton beam delivered by the MC-40 cyclotron - Maria Rita Fabbrizi; Jonathan R. Hughes; Leah D. Punshon; Laura Hawkins; Vasily Sorokin; Alice Ormrod; Emma Melia; Karthik Vaidya; Carlos P. Rubbi; Ben Phoenix; Mark A. Hill; Jason L. Parsons (Cell Death Discovery)
Abstract Proton beam therapy (PBT) is a targeted radiotherapy treatment that can deliver the majority of the radiation dose to the tumour being treated via the Bragg peak. However, there is biological and clinical uncertainty of PBT due to the increases in linear energy transfer (LET) at and around the Bragg peak. Through radiobiological characterisation of a 28 MeV pristine proton beam at several positions relative to the Bragg peak, we demonstrate that there are decreases in survival of head and neck squamous cell carcinoma (HNSCC) and HeLa cells relative to increasing LET. Through monitoring DNA damage using γH2AX/53BP1/OGG1 foci via immunofluorescence microscopy and different versions of the comet assay, we show that increasing relative biological effectiveness (RBE) is directly associated with predominantly DNA single strand breaks that were more difficult to repair and persisted, in addition to a strong correlation with increases in the presence of more persistent complex DNA damage. Increasing frequencies of micronuclei as a marker of chromosomal damage were also observed as a function of LET. Our data demonstrate that increases in LET across the Bragg peak can create changes in the DNA damage spectrum that drive the radiobiological response.